1995
DOI: 10.1016/s0002-9610(99)80161-5
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of intestinal dysmotility and stasis by octreotide early after small-bowel autotransplantation in dogs

Abstract: BACKGROUND-Intestinal dysmotility and stasis after intestinal transplantation are considered to promote bacterial overgrowth and translocation. Two prokinetic agents, KW5139 (13-leu-motilin) and the somatostatin analogue octreotide acetate, were studied to determine whether they can ameliorate intestinal dysmotility during the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Preclinical studies on the somatostatin analogue octreotide demonstrated increased intestinal motility in dogs after small-bowel autotransplantation and amelioration of POI [48, 49]. Receptor-specific compounds (e.g., serotonin and motilin receptor agonists, dopamine and cholecystokinin-1 [CCK-1] receptor antagonists) have also demonstrated some motility-promoting activity [45, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies on the somatostatin analogue octreotide demonstrated increased intestinal motility in dogs after small-bowel autotransplantation and amelioration of POI [48, 49]. Receptor-specific compounds (e.g., serotonin and motilin receptor agonists, dopamine and cholecystokinin-1 [CCK-1] receptor antagonists) have also demonstrated some motility-promoting activity [45, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Phase I studies have demonstrated that neostigmine, an acetylcholinesterase inhibitor, increases postoperative colonic motility and tone in healthy volunteers and patients undergoing colorectal surgery [ 47 ]. Preclinical studies on the somatostatin analogue octreotide demonstrated increased intestinal motility in dogs after small-bowel autotransplantation and amelioration of POI [ 48 , 49 ]. Receptor-specific compounds (e.g., serotonin and motilin receptor agonists, dopamine and cholecystokinin-1 [CCK-1] receptor antagonists) have also demonstrated some motility-promoting activity [ 45 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the strain gauge monitoring was performed in awake animals, it required implantation of the gauges onto the intestine, perhaps therefore affecting the ordered motility of the intestine. Previous animal studies, however, have shown that motility is preserved in this setting [23]. Using the 2 modalities in conjunction arguably allows their findings to corroborate each other.…”
Section: Discussionmentioning
confidence: 73%
“…Table III summarizes the effects of SBD and SBAT on small-intestinal motility. After SBAT in dogs and rats, small-intestinal myoelectric activity is initially characterized by a virtual absence of motor activity (49,(75)(76)(77). Thereafter the autotransplanted rat or canine small bowel gradually generates the migrating myoelectric complex, which may reach the same rate as that of controls as soon as 1 to 2 weeks after the surgery (49,(77)(78)(79).…”
Section: Physiology Of the Transplanted Jejunoileummentioning
confidence: 99%
“…Pharmacologic manipulation of the transplantation-induced small-intestinal dysmotility and bacterial overgrowth, to improve absorptive function, is a very fruitful area for future investigation. In fact, intravenous octreotide appears to improve intestinal dysmotility and stasis in dogs after SBAT (76). However, whether the improved motility affects small-intestinal absorptive function remains unexplored.…”
Section: Physiology Of the Transplanted Jejunoileummentioning
confidence: 99%